Determining the Physical and Chemical Characteristics of Groundwater in 4th District of Kabul City, Afghanistan: A cross-sectional study - Sharifi, Fahima; Salih, Mohibullah (Technium BioChemMed, 2021)
The 4th district is one of the most populated residential and commercial areas of the Kabul city. This increase in population has created many problems both in terms of environmental protection and drinking-water supply. In addition, the increase in construction of low quality buildings on planned and unplanned areas, excavation of deep or semi-deep wells, and the absence of proper sewage recycling systems have negative effects on the quality of drinking-water. The results of quantitative and qualitative researches on drinking or wholesome water show that the physical and chemical parameters such as electrical conductivity, turbidity, pH, Cl, and total hardness of deep-wells water in the district of Kabul does meet the WHO and ANSA standards and have almost better quality. However, most samples of the semi-deep water wells in 4th district of Kabul city do not match the WHO and ANSA standards. Thus, the presence of dissolved elements such as calcium, chlorine, and magnesium in drinking water resources show that the drinking-water of some of the mentioned areas do not have good quality which can cause environmental and health problems. This study is aimed on the assessment and determination of physical and chemical characteristics of drinking groundwater in different parts of the 4th district of Kabul city, Afghanistan. Method: An observational cross-sectional study was conducted over a period of two-month from April the first to June the 6, 2021 in different parts of the 4th district of Kabul city, Afghanistan. A total of 64 samples were collected. The data was entered and analyzed using SPSS 26. Frequencies and percentages were calculated for variables. Minimum, maximum, mean and standard deviation were calculated for continuous variables. Results: A total of 64 water samples (32 samples from deep & 32 samples form shallow wells) were collected from the 4th district of Kabul city, Afghanistan. The physical and chemical parameters, in shallow wells in 17 samples (53%) were normal and in 15 samples (47%) were found in abnormal ranges according to WHO and ANSA standards. In deep-water wells, the physical and chemical parameters in 27 Samples (84%) were normal and in 5 samples (16%) were found and calculated in abnormal ranges.